Comment on "Energy and entropy analysis of closed adiabatic expansion based trilateral cycles" by Ramon Ferreiro Garcia, Jose Carbia Carril, Javier Romero Gomez, Manuel Romero Gomez [Energy Convers. Manage. 119 (2016) 49–59]. (1st September 2016) - Stouffs, Pascal
Abstract: The authors of the above mentioned paper claim that "recent developments related to the performance of thermal cycles composed of closed processes have led to the exceeding of the Carnot factor" (Garcia et al., 2016). However, this unusual result is based on an erroneous analysis of the proposed trilateral cycles. The authors forget to take into account the compression work of the working fluid. By considering both the expansion and the compression work of the cycle, the correct thermal efficiency is far lower than the Carnot efficiency.